Immunogenicity and Therapeutic Efficacy of a Dual-Component Genetic Cancer Vaccine Cotargeting Carcinoembryonic Antigen and HER2/neu in Preclinical Models - Aurisicchio, Luigi (Mary Ann Liebert, Inc., 2014)
Several cancer vaccine efforts have been directed to simultaneously cotarget multiple tumor antigens, with the intent to achieve broader immune responses and more effective control of cancer growth. Genetic cancer vaccines based on in vivo muscle electro-gene-transfer of plasmid DNA (DNA-EGT) and adenoviral vectors represent promising modalities to elicit powerful immune responses against tumor-associated antigens (TAAs) such as carcinoembryonic antigen (CEA) and human epidermal growth factor receptor-2 (HER2)/neu. Combinations of these modalities of immunization (heterologous prime–boost) can induce superior immune reactions as compared with single-modality vaccines. We have generated a dual component–dual target genetic cancer vaccine consisting of a DNA moiety containing equal amounts of two plasmids, one encoding the extracellular and transmembrane domains of HER2 (ECD.TM) and the other encoding CEA fused to the B subunit of Escherichia coli heat-labile toxin (LTB), and of an adenoviral subtype 6 dicistronic vector carrying the same two tumor antigens gene constructs. The CEA/HER2 vaccine was tested in two different CEA/HER2 double-transgenic mouse models and in NOD/scid-DR1 mice engrafted with the human immune system. The immune response was measured by enzyme-linked immunospot assay, flow cytometry, and ELISA. The CEA/HER2 vaccine was able to break immune tolerance against both antigens. Induction of a T cell and antibody immune response was detected in immune-tolerant mice. Most importantly, the vaccine was able to slow the growth of HER2/neu(+) and CEA(+) tumors. A significant T cell response was measured in NOD/scid-DR1 mice engrafted with human cord blood cells. In conclusion, the CEA/HER2 genetic vaccine was immunogenic and able to confer significant therapeutic effects. These data warrant the evaluation of this vaccination strategy in human clinical trials.